If ever I should love you [large type] - Maxwell, Cathy (Maxwell, Cathy. Spinster heiresses, 2018)
"London, 1813. Roman Gilchrist, newly named tenth Earl of Rochdale, needs a wife who will exchange her fortune for his family name. Leonie Charnock, one of the season's 'Spinster Heiresses, ' agrees with one condition: there will be a wedding but no bedding. But it's a condition the new Countess Rochdale isn't sure even she can keep it"--